2015
DOI: 10.1016/j.cyto.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M binds to extracellular matrix in a bioactive conformation: Implications for inflammation and metastasis

Abstract: Oncostatin M (OSM) is an interleukin-6-like inflammatory cytokine reported to play a role in a number of pathological processes including cancer. Full-length OSM is expressed as a 26 kDa protein that can be proteolytically processed into 24 kDa and 22 kDa forms via removal of C-terminal peptides. In this study, we examined both the ability of OSM to bind to the extracellular matrix (ECM) and the activity of immobilized OSM on human breast carcinoma cells. OSM was observed to bind to ECM proteins collagen types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 96 publications
2
41
0
Order By: Relevance
“…Of note, OSM protein staining was diffuse in the injured muscle of SCI mice developing HO, consistent with the observation that bioactive OSM binds to extracellular matrix proteins, such as collagen I and laminin (59), which are abundant in muscle, particularly at acidic pH, as found in inflamed or injured tissues. Of note, deletion of the Osmr gene did not completely ablate NHO, as observed following in vivo macrophage depletion with clodronate liposomes (11).…”
Section: Discussionsupporting
confidence: 55%
“…Of note, OSM protein staining was diffuse in the injured muscle of SCI mice developing HO, consistent with the observation that bioactive OSM binds to extracellular matrix proteins, such as collagen I and laminin (59), which are abundant in muscle, particularly at acidic pH, as found in inflamed or injured tissues. Of note, deletion of the Osmr gene did not completely ablate NHO, as observed following in vivo macrophage depletion with clodronate liposomes (11).…”
Section: Discussionsupporting
confidence: 55%
“…Tran et al suggested that OSM overexpression in tumor cells was found in keratoacanthoma (a low-grade tumor) and in dermal squamous cell carcinoma, relative to normal tonsillar controls [18]. By contrast, Ryan et al could not demonstrate OSM expression in colon cancer cells, but strong expression in tumorinfiltrating neutrophils, indicating that these neutrophils were the main source of OSM secreted in this cancer [8]. Thus, not only immune cells, but also environmental factors such as HPV infection may induce OSM overexpression in oral keratinocytes and oral cancer cells.…”
Section: Discussionmentioning
confidence: 86%
“…It is produced by various immune cells, such as activated T lymphocytes, monocytes, neutrophils and macrophages [6]. OSM is also produced in epithelial cells, keratinocytes and cancer cells [7,8]. OSM stimulates the target cells in both autocrine and paracrine modes via binding to appropriate receptors (OSMR/gp130 and LIFR/ gp130) and subsequently induces many signaling cascades to promote several biological consequences such as growth inhibition, inflammatory response and cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that OSM in the TME contributes to tumor progression. 1,[19][20][21][22][23][24]28,33,74,[87][88][89][90][91][92][93] For example, in addition to the increased OSM levels in the breast TME, breast cancer cells also display elevated OSMR expression levels, which is associated with adverse clinical outcomes. 32,71,83,88,92,94 Notably, the more aggressive basal-like or triple-negative breast cancer subtype expresses markedly higher levels of OSMR when compare with the less aggressive luminal subtype.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Elevated levels of OSM in the TME are associated with highly aggressive metastatic cancers, increased risk of tumor recurrence, and a poor prognosis. [19][20][21][22][23][24] In breast cancer, OSM is concentrated at the invasive edges of highly metastatic tumors where cells often display mesenchymal cell characteristics and express the cancer stem cell marker CD44. 22,25 Whereas OSM drives proliferation, epithelial-mesenchymal transition (EMT), invasion, and metastasis in breast cancer cells and transformed human mammary epithelial cells (HMEC), it engages senescence in normal and non-transformed HMEC.…”
Section: Introductionmentioning
confidence: 99%